Financial Management of Zakat Funds Based on the BAZNAS Management Information System (SIMBA) in Enhancing Accountability (A Case Study of BAZNAS Kota Surabaya) - Luthfiyatul Kamalia; Novie Andriani Zakariya (CV. Satria Jaya, 2025)
This study aims to analyze zakat fund financial management based on the BAZNAS Management Information System (SIMBA) in enhancing the accountability of zakat fund management at BAZNAS Kota Surabaya. The study employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and analysis of institutional financial documents. Research informants consist of financial managers and relevant staff directly involved in the recording, supervision, and reporting of zakat funds. The findings indicate that SIMBA functions as the primary system in ensuring standardization, accountability, and formal zakat financial reporting in accordance with national BAZNAS regulations. However, in daily operational practices, BAZNAS Kota Surabaya continues to utilize manual spreadsheet-based records as a supporting tool to meet the needs for flexibility, rapid data recapitulation, and internal control. The use of this dual-system reflects a digital transition phase, where the effectiveness of financial management is determined not only by the existence of information systems but also by human resource capacity, operational discipline, and internal supervision mechanisms. Despite challenges such as limited human resources and technical constraints in using SIMBA, overall zakat fund financial management at BAZNAS Kota Surabaya has been implemented effectively and has contributed to improved transparency and public trust. This study emphasizes that the continuous development of SIMBA, making it more adaptive to regional operational needs, is a crucial factor in strengthening governance and accountability within zakat institutions in the digital era.